Critiquing the evolution of maternity care preferences research: A systematic mixed studies review. (August 2022) - Bull, Claudia; Creedy, Debra K.; Gamble, Jenny; Toohill, Jocelyn; Karger, Shae; Callander, Emily J.
Highlights: A woman's ability to make decisions about her maternity care is limited by her knowledge of available resources. We identified and described research about women's preferences for maternity care published since 2010. Most studies did not provide women with information to support their decision-making about their preferences. Women's preferences in the context of unrestricted access to maternity care are largely unknown. Understanding women's information needs to support decision-making about their preferences is critical. Abstract: Objective: Whether women's preferences for maternity care are informed remains unclear, suggesting that maternal preferences may not accurately represent what women truly want. The aim of this study was to understand and critique research on women's maternity care preferences published since 2010. Design: Systematic mixed studies review. CINHAL, EMBASE, MEDLINE, and ProQuest Nursing and Allied Health electronic databases were searched from January 2010 to April 2022. Findings: Thirty-five articles were included. Models of care and mode of birth were the most frequently investigated preference topics. Roughly three-quarters of included studies employed a quantitative design. Few studies assessed women's baseline knowledge regarding the aspects of maternity care investigated, and three provided information to help inform women's maternity care preferences. Over 85% of studies involved women who were either pregnant at the time of investigation or had previously given birth, and 71% employed study designs where women were required to select from pre-determined response options to describe their preferences. Two studies asked women about their preferences in the face of unlimited access and availability to specific maternity care services. Key conclusions: Limited provision of supporting information, the predominant inclusion of women with experience using maternity care services, and limited use of mixed methods may have hindered the collection of accurate information from women about their preferences. Implications for practice: Women's maternity care preferences research since 2010 may only present a limited version of what they want.